A tale of two sisters. Issue 4 (26th March 2004) - Gaya, D R; McLay, A L C; Oien, K A; Spooner, R J; Reilly, T G
Abstract : Hereditary haemochromatosis is the most common inherited disorder in white populations, whereas non-alcoholic steatohepatitis (NASH) is becoming the most common reason for referral for investigation of abnormal liver function tests (LFTs). This report describes two sisters, from similar environments, who were referred to the clinic after being found to be C282Y homozygotes and to have abnormal LFTs. One sister had developed features of haemochromatosis and the other had developed NASH. These cases illustrate the potential non-penetrance of HFE gene mutations and the need to investigate abnormal LFTs fully, even when there is a positive genetic test at the outset.